The connection between the Cegrell classes and compliant functions - Czyz (Mathematica Scandinavica)
In this article the connection between the Cegrell classes and compliant functions is studied. A suitable norm is constructed which makes the compliant functions into a Banach space. As an application a characterization of the Dirichlet problem for pluriharmonic functions is achieved. Explicit examples of non-compliant functions will be constructed and a sufficient condition for compliance will be proved.